Construction of Driving Seat Frame and 2-Dof Motion Simulator - Saadon, Intan Mastura (International Journal of Integrated Engineering, 2020)
Driving simulators are increasingly being used as a didactic tool in car racing games because it offers virtual driving experience to users. However, existing driving simulators are found in market at high cost. This paper proposes the design and development of a low cost 2-DOF driving motion simulator with the interface from SimTools. The driving simulator comprises a steering wheel, a pedal and simulator software. When the steering wheel is turned in the racing simulator Live for Speed, it controls the angle of the driver’s seat upraising. The input data from the steering wheel is derived using SimTools, which extracts the motion data from the racing simulator. Potentiometer is used as the feedback sensor that manipulates the data from SimTools to control the angle of the dc motor driver rotation. The motion is created using the rotation of two dc motors that actuate the car seat frame. Moto Monster motor driver which supports 30A of current is used to control both of the dc motors using Arduino microcontroller. The angle control of the driver’s seat is proportional to the input data from steering wheel. This paper contributes the basic idea on building a low cost motion simulator.